Production of mutant plants conducive to salt tolerance - Nabors, Murray W., author; Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1976)
Much successful work has been done on altering the environment by irrigation to increase the amount of land in agricultural production, however the costs may increase as suitable water becomes more difficult to develop. The alternative may be to adjust the plants to accept lower quality water through selection for appropriate spontaneous mutants. Methods for the selection of desirable spontaneous mutants require the application of environmental pressure to give the mutant a competitive advantage and also require the examination of millions of individual plants. To accomplish this in field trials is time consuming and costly. Instead this project employs individual cells in tissue culture where ten million cells occupy 100 ml and each cell effectively is a plant, because a plant can be regenerated from an individual cell. Plant properties such as salt tolerance which is exhibited on the cellular level can be selected in tissue culture at much less cost due to the small scale required. The focus of this project has been toward the selection of salt mutants. Two lines of tobacco cells, tolerant to NaCl levels of 8000 ppm, have been selected while normal tolerance to NaCI in this species is 800 ppm. Plants have been regenerated from the tissue cultures at many levels of NaCI tolerance between these extremes, and these plants are currently being tested for NaCl tolerance and for mutation inheritability. Although practical tolerance needs may not exceed 2000-3000 ppm, the higher ranges of salt tolerance may yield mutants with better yields at the moderate tolerance levels. Considerable progress has been made toward tissue culture mutant selection systems for oats, wheat, soybean, corn, and sugar beets. Selection for salt tolerant mutants is currently underway for both oats and wheat.
July 1976.
Keywords: Field crops -- Varieties; Plants -- Effect of salt on; Plant mutation; Plant tissue culture